STRATEGI PROMOSI EVENT NAMASTE FESTIVAL - Arie Wibowo (Universitas Mercu Buana, 2015)
Promotion Strategy is the method that you use to promote the product. If we use the wrong promotion strategy, it will bring the disadvantage for the product and company. And on the contrary, if we are using the right promotion strategy, then it will bring the benefit for the product selling as did by Namaste Festival Event. This research was conducted in order to discover how promotion strategy of Namaste Festival Event to attract Yoga market by using promotion strategy theory. This research was guided by a qualitative approach with descriptive research in particular. The method being used was case study by conducting in-depth interviews. This research enabled the writer to discuss about the promotion strategy that being used by Namaste Festival event to increase the number of visitor. Therefore the researcher will able to get view on how PT Namaste Jaya Aditi as the organizer could run the promotion to get high number of visitor. After conducting an analysis, the main conclusion of this research is that the promotion strategy that been used by Namaste Festival organize is integrated several promotion activities such as online marketing, pre event road show, selling promotion, advertising (television and media printing) & publicity. The result of this research is also said that promotion strategy that been use has an important role to attract visitor to participate in the event.Strategi Promosi adalah metode yang Anda gunakan untuk mempromosikan produk. Jika kita menggunakan strategi promosi yang salah, maka akan membawa kerugian bagi produk dan perusahaan. Dan sebaliknya, jika kita menggunakan strategi promosi yang tepat, maka akan membawa keuntungan bagi penjualan produk seperti yang dilakukan oleh Namaste Festival Event. Penelitian ini dilakukan untuk mengetahui bagaimana strategi promosi Namaste Festival Event untuk menarik pasar Yoga dengan menggunakan teori strategi promosi. Penelitian ini dipandu oleh pendekatan kualitatif dengan penelitian deskriptif pada khususnya. Metode yang digunakan adalah studi kasus dengan melakukan wawancara mendalam. Penelitian ini memungkinkan penulis untuk membahas tentang strategi promosi yang digunakan oleh festival Namaste Festival untuk meningkatkan jumlah pengunjung. Oleh karena itu peneliti dapat melihat bagaimana PT Namaste Jaya Aditi sebagai penyelenggara dapat menjalankan promosi untuk mendapatkan jumlah pengunjung yang tinggi. Setelah melakukan analisis, kesimpulan utama dari penelitian ini adalah bahwa strategi promosi yang telah digunakan oleh Namaste Festival organizer mengintegrasikan beberapa kegiatan promosi seperti pemasaran online, pre event road show, promosi penjualan, periklanan (media cetak dan televisi) & publisitas. . Hasil penelitian ini juga mengatakan bahwa strategi promosi yang telah digunakan memiliki peran penting untuk menarik pengunjung untuk berpartisipasi dalam acara tersebut.